The dead of night - Marsden, John, 1950- (New York; Scholastic, Inc., 1994)
Six determined Australian teenagers try to find their missing friends while continuing to resist the enemies who have invaded their country
"First published in Australia in 1994 by Pan Macmillan Publishers"--T.p. verso
Sequel to: Tomorrow, when the war began
Keywords: Survival -- Fiction; War -- Fiction; Australia -- Fiction